The scarecrow walks at midnight - Stine, R. L.; Copyright Paperback Collection (Library of Congress) (New York, NY : Scholastic Inc., 1994)
Jodie is staying with her grandparents on their farm and sees the scarecrows "come alive!"
"An Apple paperback."
Includes a detachable bookmark.
G3
Keywords: Scarecrows -- Fiction; Grandparents -- Fiction; Farm life -- Fiction; Horror stories